Bulan Restu bus ticketing system (online) - Sarawanakumar, Segar (2012)
Traveling is a large growing business in Malaysia and other countries.Bus reservation system deals with maintenance of records of details of each passenger who had reserved a seat for a journey.It also includes maintenance of information like schedule and details of each bus.We observed the working of the Bus reservation system and after going through it,we get to know that there are many operations, which they have to do manually.It takes a lot of time and causes many errors.Due to this,sometimes a lot of problems occur and they were facing many disputes with customers.To solve the above problem,and further maintaining records of items,seat availability for customers,price of per seat, bill generation and other things,we are offering this proposal of reservation system.One of the bus company which have same kind of problem is Bulan Restu .In Bulan Restu bus ticketing system there has been a collection of buses,agent who are booking tickets for customer’s journey which give bus number and departure time of the bus.According to its name it manages the details of all agent,tickets,rental details,and timing details and so on.It also manages the updating of the objects.In the tour detail there is information about bus,who has been taking customers at their destination,it also contain the detailed information about the customer,who has been taken from which bus and at what are the number of members he or she is taking his/her journey.This section also contain the details of booking time of the seat(s)or collecting time of the tickets,this section also contain the booking date and the name of agent which is optional,by which the customer can reserve the seats for his journey.In Bus no category it contains the details of buses which are old/new.New buses are added with the details with bus no,from city to the city,type of the bus, rent of a single seat,if the bus has sleeper than the cost of sleeper,if the cabin has the facility for sitting than the cost of cabin seats,tour timings of the new bus has also been stored.The main objective of this project is to provide the better work efficiency,security,accuracy, reliability,feasibility.The error occurred could be reduced to nil and working conditions can be improved.By using this software,we can reserve tickets from any part of the world, via internet.This project provides and checks all sorts of constraints so that user does give only useful data and thus validation is done in an effective way.